Step-by-step explanation:
position your compass at point A and using the same distance mark arcs on line AB(mark the point it meets the line D)and AC(mark the meeting point of the arc and the line E).Place your compass at D and draw an arc at the middle of the angle,using the same measurements position your compass at point E and draw an arc.Where the two arcs meet label F using a ruler draw a straight line from F to meet point A.
Note;the width of the compass when making the arcs should be the same always
and the Aegean Sea is located at
On the map above, the Black Sea is located at
A Letter A Letter C
B. Letter C Letter B
C Letter A Letter B
D. Letter B Letter A
Answer:
The answer to your question is C.
Step-by-step explanation:
Have a nice day :)
I will give you 10B points plus mark someone again for the Brainliest if you get this right.
Answer:
C
Step-by-step explanation:
Option c gives the actual representation of the question
The maximum point on the graph of the equation
y = f(x) is (2,-3). What is the maximum point on
the graph of the equation y=f(x-4)?
Answer:
(6, - 3 )
Step-by-step explanation:
Given f(x) then f( x + c) represents a horizontal translation of f(x)
• If c > 0 then a shift to the left of c units
• If c < 0 then a shift to the right of c units, thus
y = f(x - 4) represents a shift to the right of 4 units, so
(2, - 3 ) → (2 + 4, - 3 ) → (6, - 3 )
The maximum point on the graph after translation y = f( x -4) is (6 , -3)
What is translation of a graph?Translation of a graph is the movement of the graph either in horizontal direction or vertical direction .
Horizontal translation to the left is given by f (x+ c) ,c >0
: (x, y) → (x- c , y)
Horizontal translation to the right is given by f (x- c) ,c >0
: (x, y) → (x+ c , y)
Given that the maximum point on the graph of the equation
y = f(x) is (2,-3)
To find the maximum point on the graph of the equation y = f(x-4)
f(x -4) is Horizontal Translation to the right with 4 units , c= 4
then (x, y) → (x+ c , y)
Thus the maximum point (2,-3) is moved to ( 2 +c , -3)
⇒ (2+ c , -3) = (2+4 , -3) = ( 6 , -3)
Therefore, the maximum point of the graph of the equation y = f(x-4) becomes (6,-3)
Also, Learn more abut translation of graphs from the link below:
https://brainly.com/question/11805053
#SPJ5
simplify √x^2+6x+9 if x≥3
Answer:
simplified expression for √x^2+6x+9 if x≥3
is x+3
Step-by-step explanation:
[tex]\sqrt{x^2+6x+9} \\=>\sqrt{x^2+3x+3x+9} \\=>\sqrt{x(x+3)+3(x+3)} \\=>\sqrt{(x+3)(x+3)} \\=>\sqrt{(x+3)^2}\\=>(x+3) \ or -(x+3)[/tex]
but given that x≥3
then we have to negate solution -(x+3)\
Then simplified expression for √x^2+6x+9 if x≥3
is x+3